# Solve for b -(7-4b)=9

-(7-4b)=9
Multiply each term in -(7-4b)=9 by -1
Multiply each term in -(7-4b)=9 by -1.
-(7-4b)⋅-1=9⋅-1
Simplify -(7-4b)⋅-1.
Apply the distributive property.
(-1⋅7-(-4b))⋅-1=9⋅-1
Multiply.
Multiply -1 by 7.
(-7-(-4b))⋅-1=9⋅-1
Multiply -4 by -1.
(-7+4b)⋅-1=9⋅-1
(-7+4b)⋅-1=9⋅-1
Apply the distributive property.
-7⋅-1+4b⋅-1=9⋅-1
Multiply.
Multiply -7 by -1.
7+4b⋅-1=9⋅-1
Multiply -1 by 4.
7-4b=9⋅-1
7-4b=9⋅-1
7-4b=9⋅-1
Multiply 9 by -1.
7-4b=-9
7-4b=-9
Move all terms not containing b to the right side of the equation.
Subtract 7 from both sides of the equation.
-4b=-9-7
Subtract 7 from -9.
-4b=-16
-4b=-16
Divide each term by -4 and simplify.
Divide each term in -4b=-16 by -4.
-4b-4=-16-4
Cancel the common factor of -4.
Cancel the common factor.
-4b-4=-16-4
Divide b by 1.
b=-16-4
b=-16-4
Divide -16 by -4.
b=4
b=4
Solve for b -(7-4b)=9

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top